Protein and Mitochondria Quality Control Mechanisms and Cardiac Aging - Rajeshwary Ghosh; Vishaka Vinod; J. David Symons; Sihem Boudina (Cells, 2020)
Cardiovascular disease (CVD) is the number one cause of death in the United States. Advancing age is a primary risk factor for developing CVD. Estimates indicate that 20% of the US population will be ≥65 years old by 2030. Direct expenditures for treating CVD in the older population combined with indirect costs, secondary to lost wages, are predicted to reach $1.1 trillion by 2035. Therefore, there is an eminent need to discover novel therapeutic targets and identify new interventions to delay, lessen the severity, or prevent cardiovascular complications associated with advanced age. Protein and organelle quality control pathways including autophagy/lysosomal and the ubiquitin-proteasome systems, are emerging contributors of age-associated myocardial dysfunction. In general, two findings have sparked this interest. First, strong evidence indicates that cardiac protein degradation pathways are altered in the heart with aging. Second, it is well accepted that damaged and misfolded protein aggregates and dysfunctional mitochondria accumulate in the heart with age. In this review, we will: (i) define the different protein and mitochondria quality control mechanisms in the heart; (ii) provide evidence that each quality control pathway becomes dysfunctional during cardiac aging; and (iii) discuss current advances in targeting these pathways to maintain cardiac function with age.